2014
DOI: 10.1186/s12868-014-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the retina of Niemann-pick type C 1 mutant mice

Abstract: BackgroundNiemann-Pick type C1 (NPC1) disease is an inherited lysosomal storage disease caused by mutation of the Npc1 gene, resulting in a progressive accumulation of unesterified cholesterol and glycolipids in lysosomes of multiple tissues and leading to neurodegeneration and other disease. In Npc1 mutant mice, retinal degeneration including impaired visual function, lipofuscin accumulation in the pigment epithelium and ganglion cells as well as photoreceptor defects has been found. However, the pathologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…In GD ganglion cell layer atrophy was found in GD patients but also in asymptomatic mutation carriers [17]. Indeed, animal studies in NPC1-mutant mice demonstrated preclinical retinal degeneration and lipofuscin accumulation in the pigment epithelium and ganglion cells, electrodense inclusions in various cell types, photoreceptor defects, and hyperactivity of glial cells [42,46], as well as optic nerve pallor and per macular grey discoloration [47]. Given the pathomechanistic similarities between NPC and GD, we encourage additional work in NPC heterozygotes to shed further light on potential similar risks.…”
Section: Discussionmentioning
confidence: 99%
“…In GD ganglion cell layer atrophy was found in GD patients but also in asymptomatic mutation carriers [17]. Indeed, animal studies in NPC1-mutant mice demonstrated preclinical retinal degeneration and lipofuscin accumulation in the pigment epithelium and ganglion cells, electrodense inclusions in various cell types, photoreceptor defects, and hyperactivity of glial cells [42,46], as well as optic nerve pallor and per macular grey discoloration [47]. Given the pathomechanistic similarities between NPC and GD, we encourage additional work in NPC heterozygotes to shed further light on potential similar risks.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities are likely associated with an impairment of various sensory pathways, as already indicated by the deficit of auditory [ 11 , 49 ] and olfactory [ 50 ] systems in Npc1 −/− mice and of multisensory processing in NPC patients [ 51 ]. As for the visual system of Npc1 −/− mice, retinal cellular and functional defects were recently described [ 19 , 20 ], but the functional integrity of their visual pathway has not been investigated yet. Now addressing this issue, we report that the transmission of visual stimuli from retina to visual cortex is strongly influenced by the lack of Npc1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the auditory pathway, the cellular dysfunctions of Npc1 −/− mouse retina and dLGN suggest that the visual pathway is also affected in NPC1 disease. Morphological and functional anomalies of the retina of these mice were recently reported, showing age-related degeneration of photoreceptors and a number of anomalies in several cell types of the visual system, including increased autophagy in retinal ganglion cell layer (GCL), electron-dense inclusions in bipolar and Müller cells, abnormal arborization of horizontal and amacrine cells, altered myelination, dilated axons of the optic nerve [ 19 ] and reduced amplitude of electroretinogram (ERG) responses [ 20 ]. However, studies investigating the functional integrity of the visual pathway from retina to visual cortex are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Then, cardiac perfusion with phosphate-buffered saline (PBS, pH = 7.4) was followed by 4% paraformaldehyde (PFA) in 0.1 M PBS. As previously described by our group [ 50 ] after perfusion and preparation liver samples were excised and postfixed in 0.1 M phosphate buffer containing 2.5% glutaraldehyde for at least 24 h at 4 °C. Thereafter, the specimens were osmicated, washed, block contrasted with 2% aqueous uranyl acetate, dehydrated through a graded series of ethanol, and embedded in Epon 812 (Plano GmbH, Marburg, Germany).…”
Section: Methodsmentioning
confidence: 99%